Radio chemotherapy for Squamous Cell Carcinoma of Hypopharynx in One Patient with Ehler Danlos Disease - Collineau, Berenice; Padovani, Laetitia; Fahkry, Nicolas; Richard, Marie-Aleth; Busa, Tiffany; Pougnet, Isabelle (Archives of Clinical and Medical Case Reports, 2024)
Head and neck squamous cell carcinomas are frequent, in most cases developed in a context of alcohol and tobacco consumption. Therapeutic options for localized head and neck carcinomas are surgery, if possible, and radiotherapy with or without chemotherapy. Ehler-Danlos syndrome is a rare group of disease, clinically and genetically heterogeneous, characterized by connective tissue fragility. Management of adverse event during radiotherapy remains a challenge, especially for people known to have connective tissue disorder. Here, we report a case of a man suffering from periodontal Ehler Danlos syndrome, treated with concomitant radiochemotherapy, with adapted radiotherapy regimen, for hypopharyngeal squamous cell carcinoma.